Arrhythmia insensitive rapid cardiac T1 mapping pulse sequence. Issue 5 (27th December 2012) - Fitts, Michelle; Breton, Elodie; Kholmovski, Eugene G.; Dosdall, Derek J.; Vijayakumar, Sathya; Hong, Kyung P.; Ranjan, Ravi; Marrouche, Nassir F.; Axel, Leon; Kim, Daniel
<x xml:space="preserve">Abstract</x> Purpose To develop an arrhythmia‐insensitive rapid (AIR) cardiac T1 mapping pulse sequence for quantification of diffuse fibrosis. Methods An arrhythmia‐insensitive cardiac T1 mapping pulse sequence was developed based on saturation recovery T1 weighting, which is inherently insensitive to heart rate and rhythm, and two single‐shot balanced steady‐state free precession image acquisitions with centric k‐space ordering, where T1 calculation is inherently insensitive to T2 effects. Its performance against conventional cardiac T1 mapping based on inversion recovery (i.e., MOLLI) is compared. Phantom experiments (T1 ranging from 535 to 2123 ms) were performed with heart rate and rhythm simulated at 60 and 120 beats per minute (bpm) and arrhythmia using an external triggering device. Ten human subjects and 17 large animals were scanned precontrast and 5, 10, and 15 min after contrast agent administration. Results Compared with the reference T1 mapping, AIR yielded lower normalized root‐mean‐square error than MOLLI (8% vs. 3%, respectively, at 60 bpm, 28% vs. 3%, respectively, at 120 bpm, and 22% vs. 3%, respectively, at arrhythmia). In vivo studies showed that T1 measurements made by MOLLI and AIR were strongly correlated (r = 0.99) but in poor agreement (mean difference = 161.8 ms, upper and lower 95% limits of agreements = 347.5 ms and −24.0 ms). Conclusion Our AIR pulse sequence may be clinically useful for assessment of diffuse myocardial fibrosis in patients. Magn Reson Med 70:1274–1282, 2013. © 2012 Wiley Periodicals, Inc.